Consumo y confianza de los cibermedios en Perú. Un estudio sobre los estudiantes universitarios - Ibáñez, D.B. (2018)
The virtual public space tends to be articulated as an extension of the contemporary public sphere. However, this is a process that is not being developed horizontally at a global level, there are countries that, like Peru, are identified by the predominant mediation of traditional media, as a consequence of the digital divide, according to which approximately half of the population is still not connected. This study presents the results of a survey of 720 university students in Peru, and our interest lies in describing aspects such as the relationship between trust and consumption of digital media in this country; the main characteristics required of an informative website; the most used interaction mechanisms; and, ultimately, how a group so relevant to Peruvian democracy, such as young university students, tends to channel their participation and experience online.